Age and sex differences in blood pressure regulation: A focus on the vascular baroreflex limb - Darcianne K. Watanabe; Suzi Hong; DeWayne P. Williams; Jordan Kohn; Julian Koenig; Gustavo A. Reyes del Paso; Julian F. Thayer (Physiological Reports, 2025)
Abstract Despite the vasculature's role in long‐term blood pressure (BP) regulation, limited work exists on vascular baroreflex function. This study focused on hypothesized age and sex differences in the vascular‐sympathetic baroreflex limb and explored the role of hormone replacement therapy (HRT). Resting cardiac and hemodynamic measures were recorded. Baroreflex sensitivity (BRS) and baroreflex effectiveness (BEI) were calculated for each baroreflex limb (cardiac, myocardial, and vascular). In younger adults, women had significantly lower SBP, total peripheral resistance (TPR), and vascular‐BEI than men (r's > 0.245, p's < 0.012). In older adults with managed‐hypertension, post‐menopausal women had significantly higher SBP, TPR, and vBEI, than men (r's > 0.228, p's < 0.018), while younger women had significantly higher vBRS (r's > 0.199, p's < 0.027) and lower TPR (r's > 0.281, p's < 0.002). Younger men showed significantly higher vascular‐BRS and vascular‐BEI (r's > 0.318, p's < 0.002), higher TPR and TPR‐variability (r's > 0.314, p ≤ 0.003), and lower SBP (r's > 0.295, p's < 0.005) than older men. Compared to non‐HRT women, HRT‐women had only significantly lower SBP (r = 0.243, p = 0.035). We provide the first evidence of age and sex differences in vascular baroreflex‐mediated BP control using the sequence method.